Toward a Catalytic Atroposelective Synthesis of Diaryl Ethers Through C(sp2)–H Alkylation with Nitroalkanes - Dinh, Andrew N.; Noorbehesht, Ryan R.; Toenjes, Sean T.; Jackson, Amy C.; Saputra, Mirza A.; Maddox, Sean M.; Gustafson, Jeffrey L. (Synlett, 2018)
We report studies toward a small-molecule-catalytic approach to access atropisomeric diaryl ethers that proceeds through a C(sp2)–H alkylation using nitroalkanes as the alkyl source. A quaternary ammonium salt derived from quinine, containing a sterically hindered urea at the C-9 position, was found to effect atroposelective C(sp2)–H alkylation with moderate to good enantioselectivities across several naphthoquinone-containing diaryl ethers. Products could then be isolated in >95:5 er after one round of trituration. For several substrates that were evaluated, we obtained nitroethylated products in similar yields and selectivities.
Keywords: atropisomerism; alkylation; phase-transfer catalysis; asymmetric catalysis; chirality